Phytocannabinoids Unraveling the Complex Chemistry and Pharmacology of Cannabis sativa - Kinghorn, A. Douglas; Falk, Heinz; Gibbons, Simon; Kobayashi, Jun'ichi.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The book presents the current state of the art on phytocannnabinoid chemistry and pharmacology and will be of much use to those wishing to understand the current landscape of the exciting and intriguing phytocannabinoid science. The focus is on natural product cannabinoids which have been demonstrated to act at specific receptor targets in the CNS.
Phytochemistry of Cannabis sativa L -- Synthesis of Phytocannabinoids -- Molecular pharmacology of phytocannabinoids -- Molecular targets of the phytocannabionoids: a complex picture. .
Keywords: Chemistry, Organic; Medicinal chemistry; Clinical biochemistry; Organic Chemistry; Medicinal Chemistry; Medical Biochemistry